For an Impractical Past - Kellner, Hans (História da Historiografia: International Journal of Theory and History of Historiography, 2026)
Although the field of philosophy of history is unquestionably fragmented and, at present, without a center, this is not a new situation. To answer the question “what comes next?” without somehow explaining the future through the past, we need to confront the term postmodern in its original and paradoxical sense, as put forward by Jean-François Lyotard - as that which precedes and cannot yet be understood or narrativized. Thus, in the present, the “sideshadow” would prevail, which are all the possibilities that will not be accounted for in “what really happened,” but which are of great importance at the moment. This is what the article is about: the unrealized possibilities of the future rather than a narrative of succession where the future seems an inevitable derivation of the present; and how historical narrative desublimates the past in order to explain it. The proposal of an impractical past is a call for humility on the part of the historian when presenting explanations of “what happened".